The Role of Perceived Social Support on Psychological Well-Being of University Students During the COVID-19 Pandemic - Jian Xin Aw; Nor Firdous Mohamed; Bahbibi Rahmatullah (ACHSM, 2023)
Past research revealed concerns over the depressive symptoms and psychological well-being of university students. The present study utilizes a stratified random sampling to examine the role of perceived social support on psychological well-being between depressed and non-depressed university students during the COVID-19 pandemic in Malaysia. This study recruited a total  of 244 university students from different universities across Malaysia from November 2021 to July 2022 through social media such as Facebook, Instagram, and WhatsApp. A prevalence rate of 50.4% of university students was found to present significant depressive symptoms. There is a significant correlation between perceived social support and psychological wellbeing (r = 0.769, p < 0.05). Non-depressed university students reported significantly higher on their perceived social support and psychological well-being than university students with significant depressive symptoms with values of p<0.001 and p<0.043. Among depressed university students, perceived social support from friends and significant others was reported to be significantly lower than non-depressed university students with a value of p<0.001 and p<0.023. Overall, the present study discovered that a higher level of perceived social support could predict greater psychological well-being and reduced depressive symptoms among university students. Hence, perceived social support should be promoted as an effective intervention for university students due to its accessibility and cost. Future research should look into the effectiveness of perceived social support and other psychological resources for university students with different mental health concerns.